Nilai Tauhid dalam Serat Ambiya untuk Menguatkan Pendidikan Islam Berbasis Kearifan Lokal - Hesti Mulyani; Venny Indria Ekowati; Ghis Nggar Dwiadmojo; Yusi Nurcahya Dewi; Eko Gunawan (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
Tawhid education, part of Islamic education, has an important position in Javanese society, especially for Muslims. Tawhid education can be obtained in various ways from various sources, one of which is from Serat Ambiya, which is part of Javanese local wisdom. The purpose of this study is to describe and explain the values of tawhid contained in Serat Ambiya. This research uses a qualitative descriptive method with a philological approach. Data in the form of words, phrases, clauses, or sentences in the text are taken by applying the purposive sampling technique. Data collection used reading and note-taking techniques. Based on data analysis of Serat Ambiya, the values of tauhid education contained therein can be summarized as follows: the acknowledgment of Allah as the Lord of the Universe and Allah as the Creator and Provider (tauhid rububiyah); the rejection of worshiping anything other than Allah, the declaration of tauhid, the prohibition of shirk, and the recitation of the tauhid phrase (tauhid uluhiyah); as well as the establishment of Allah's eternal nature, the call to invoke Allah's name, and the glorification of Allah (tauhid asma wa sifat). Strengthening the value of tawhid through local wisdom is one of the options as part of efforts to strengthen the values of Islamic Education in Javanese society.